Peningkatan Kompetensi Guru Menyusun RPP Melalui Lesson Study di SDK Gaibhabha - Martina Nona (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
This study aims to improve the ability of SDK Ghaibhabha teachers in preparing lesson plans. This research is a school action research where the research subjects consist of 6 teachers. The data were obtained by using observation, interview and documentation techniques. The data analysis used was a qualitative descriptive analysis technique where to see the teacher's competence from cycle I to cycle II, the average percentage was used according to the teacher's RPP assessment reference guide. The results showed that there was an increase in the ability to prepare lesson plans for the Gaibhabha SDK teachers after applying lesson study for two cycles.